PENGARUH KUALITAS PELAYANAN, FAKTOR SOSIAL DAN FAKTOR PRIBADI TERHADAP KEPUTUSAN PEMBELIAN PADA PT BILLINDO UTAMA DI KOTA BATAM - Veronica, Fiona; Rustam, Triana Ananda (SCIENTIA JOURNAL, 2021)
The purpose of this research is to find out wether service quality, social factors and personal factor influence on purchasing decision at PT Billindo Utama in Batam City. The sample size is determined by using lemeshow formula and the number of samples in this research is 384 consumers. The technique of sample used accidental sampling. The influence test in this research using multiple linear analysis and determination coefficient analysis (R2), the hypothesis testing using t test and f test using the SPSS software program version 25. The result of this research indicate variable service quality, social factors and personal factor partially and simultaneously have a significant effect on purchasing decision at PT Billindo Utama in Batam City. Keywords: Personal Factor; Purchasing Decision; Service Quality; Social Factors